KONTRIBUSI SELF CONCEPT MATEMATIS DAN MATHEMATICS ANXIETY TERHADAP HASIL BELAJAR MAHASISWA - Pamungkas, Aan Subhan (Jurnal Dinamika Pendidikan, 2015)
This study examines the relationship between self-concept and mathematics anxiety towards the freshmen learning results. The method used is the correlation method which was aimed to see how strong and how much influence of self-concept and mathematics anxiety with studentsâ learning results. The population in this study were all students of mathematics education academic year 2013/2014, the study sample was taken by purposive sampling technique as many as 88 students who took the Calculus I course. The instrument used in this research is scale mathematical self-concept and mathematics anxiety scale. The results showed that there is a positive relationship between self-concept and anxiety towards math-ematics learning outcomes of students. Research showed that there was a positive and sig-nificant relationship between self-concept and anxiety mathematical mathematics with stu-dent results.Keywords : Self Concept, Anxiety Mathematics Learning Outcomes